Organizational Design and Competencies as Sources of Sustainable Competitive Advantage in a Rapidly Changing Technological Environment - Heru Muara Sidik; Eko Sulistyo Raharjo; Sarfilianty Anggiani (Publikasi Indonesia, 2024)
In today’s rapidly evolving technological landscape, organizations must navigate a multitude of challenges to maintain a sustainable competitive advantage. The interplay between organizational design and core competencies has emerged as a critical factor in fostering adaptability and innovation. This study aims to explore the significance of aligning organizational structures and processes with strategic competencies, enabling firms to respond effectively to technological disruptions and market dynamics. A comprehensive literature review drew insights from various theoretical frameworks, including the Resource-Based View, Dynamic Capabilities, and the Technology-Organization-Environment (TOE) model. Additionally, empirical evidence from industry leaders and case studies was analyzed to examine the practical implications of organizational design and competency development. The findings highlight the importance of adopting flexible and decentralized organizational structures that facilitate rapid decision-making and knowledge sharing. Furthermore, cultivating dynamic capabilities, such as adaptability, innovation, and customer-centricity, emerged as essential competencies for sustaining competitive advantage. Effective leadership and a culture that embraces change were identified as critical enablers for successful organizational transformation. The study underscores the interdependence between organizational design and competencies in navigating the complexities of a rapidly changing technological environment. By aligning these elements, organizations can enhance their responsiveness to market shifts, capitalize on emerging opportunities, and foster a culture of continuous innovation, ultimately driving sustainable competitive advantage